Internalisasi Nilai Pendidikan Agama Islam Melalui Kegiatan Kecerdasan Kinestetik (Studi Kasus di Madrasah Ibtidaiyah Kanzul Ulum Kabupaten Mojokerto) - Tamam, Mohammad Badru (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
Kinesthetic intelligence is the ability to use the whole body in expressing ideas, feelings, and using the hand to produce or transform something. this study focused on five aspects of description, namely: 1) How internalization activities kinesthetic intelligence. 2) What is the form of kinesthetic intelligence development activities in children. 3) How is the implementation of kinesthetic intelligence activity? 4) Supporting factors and inhibiting the implementation of development programs kinesthetic intelligence activities. 5) Evaluation of teachers in assisting the development of kinesthetic intelligence activities. This study qualitative descriptive case study. Research object of kinesthetic intelligence activity applied. Sources of research data: head of madrasah, deputy of curriculum affair, student affairs representative, committee of madrasah committee, teachers, BK, soft data, education law document, RKAS, kinesthetic intelligence activity list of children, data related to the internalization of the value of Islamic religious education. Data collection techniques include observation, interviews, and documentation. To abstract the field findings, the data were analyzed by data reduction, data presentation and data conclusions. Validity of data is tested by: 1) extension of study time, 2) discussion of friends, 3) triangulation, 4) verification. The results of this study indicate: (1) The Internalization of Kinesthetic Intelligence Activities. Background by the vision of Madrasah and Law no. 20 of 2003 on National Education System (2) forms of kinesthetic intelligence development activities in children which are applied, among others, introduction of madrasah, love of friends, self-care and self-cleaning, excavation of talents and interests, and public relations. (3) Implementation of kinesthetic intelligence activities work well. (4) Supporting factors and inhibiting the implementation of the kinesthetic intelligence development program: funding, student participation and pupil support. Inhibiting factors: lack of trust for guardians, limited facilities and infrastructure, and lack of student participation (5) Evaluation of teachers in assisting the development of kinesthetic intelligence activities include CIPP: a) Context Evaluation. b) Input Evaluation (Input Evaluation). c) Process Evaluation (Evaluation Process) d) Product Evaluation (Evaluation Results).